2019
DOI: 10.1002/jctb.6076
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental assessment of a miniature bioreactor equipped with a mechanical agitator and non‐invasive biosensors

Abstract: BACKGROUND: Sufficient oxygen supply and stable process control are crucial for the successful screening and process optimization of aerobic microorganisms in small-scale bioreactors. In this work, a miniature bioreactor (volume 80 mL) equipped with non-invasive biosensors was developed and characterized. RESULTS:To enable proper mixing and high oxygen transfer rate, a mechanical agitator with large diameter (0.56 tank diameter) and submerged aeration were applied. The flow fields formed in the miniature biore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(229 reference statements)
1
2
0
Order By: Relevance
“…In addition, it can be observed that the curve of aeration is slightly curved on the surface. This observation suggests that the dominant factor in the interaction is agitation, which has been confirmed by previous studies (Dixit et al, 2015;Li et al, 2019). This is in agreement with the report of Pooja Dixit et al (2015), who also found that agitation has the most decisive effect on k L a.…”
Section: Runsupporting
confidence: 92%
“…In addition, it can be observed that the curve of aeration is slightly curved on the surface. This observation suggests that the dominant factor in the interaction is agitation, which has been confirmed by previous studies (Dixit et al, 2015;Li et al, 2019). This is in agreement with the report of Pooja Dixit et al (2015), who also found that agitation has the most decisive effect on k L a.…”
Section: Runsupporting
confidence: 92%
“…Between 4 [120] and 504 [121] cores were used for the calculations. Only five of the authors stated that they had used an HPC system [44,[121][122][123][124], with the remaining authors having used desktop machines. The current versions of Ansys Fluent and Siemens Simcenter Star-CCM+ emphasised the use of graphics processing units (GPU) instead of central processing units for the calculations.…”
Section: Hardware and Softwarementioning
confidence: 99%
“…Due to the small culture volume, the collection of offline reference samples is very limited or not possible [ 2 ]. MBR reactors usually have different stirring and gassing elements [ 8 , 12 ]. In addition to temperature, pH, and the dissolved oxygen tension, the feeding strategy is known to strongly affect protein expression in E. coli [ 1 , 13 ].…”
Section: Introductionmentioning
confidence: 99%